Adonis : male physique artistry. (London : Adonis, 1962)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks
Redactie : 15 Kennington High Street, London W.8
Engels
Periodiek